(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
In the expedient we present the Urdimento Editorial Team, that is, the body of editors, associate editors, thematic dossier editors, editorial board and the body the reviewers working in the issue of Urdimento. We also introduce the editorial support team.